Association of vitamin D and fiber intake with body fat percentage and visceral fat among female factory workers in Pontianak City - Akwilina Dwi Kristisanthy; Kusnandar Kusnandar; Isna Qadrijati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Low intakes of vitamin D and fiber can lead to increased body fat and visceral fat in female factory workers. This study aimed to assess the intake of vitamin D and fiber in female factory workers and their relationship with body and visceral fat. This study employed a cross-sectional design, involving 114 female factory workers in Pontianak, West Kalimantan, from April to August 2024. Data collection for vitamin D and fiber intake was performed using the SQFFQ, whereas body fat percentage and visceral fat were measured using BIA. Data analysis was performed using Spearman's Rank Correlation test. The results showed that female workers with higher body fat had a lower intake of vitamin D and fiber. There was a significant relationship between vitamin D intake and visceral fat (rs= 0,190; p= 0,022) but no significant relationship with body fat percentage. Fiber intake was weakly inversely correlated with body fat percentage (rs= -0,176; p= 0,030) and visceral fat (rs= -0,176; p= 0,030) in female factory workers. In conclusion, vitamin D intake is positively associated with visceral fat, whereas fiber intake has a weak inverse relationship with body fat percentage and visceral fat in female factory workers in Pontianak. Efforts to increase vitamin D and fiber intake among female factory workers should be made through nutrition education and employee meal programs.